Suppression of endoplasmic reticulum stress-dependent autophagy enhances cynaropicrin-induced apoptosis via attenuation of the P62/Keap1/Nrf2 pathways in neuroblastoma - Yang, Randong; Ma, Shurong; Zhuo, Ran; Xu, Lingqi; Jia, Siqi; Yang, Pengcheng; Yao, Ye; Cao, Haibo; Ma, Liya; Pan, Jian; Wang, Jian (Frontiers in Pharmacology, 2022)
Autophagy has dual roles in cancer, resulting in cellular adaptation to promote either cell survival or cell death. Modulating autophagy can enhance the cytotoxicity of many chemotherapeutic and targeted drugs and is increasingly considered to be a promising cancer treatment approach. Cynaropicrin (CYN) is a natural compound that was isolated from an edible plant (artichoke). Previous studies have shown that CYN exhibits antitumor effects in several cancer cell lines. However, it anticancer effects against neuroblastoma (NB) and the underlying mechanisms have not yet been investigated. More specifically, the regulation of autophagy in NB cells by CYN has never been reported before. In this study, we demonstrated that CYN induced apoptosis and protective autophagy. Further mechanistic studies suggested that ER stress-induced autophagy inhibited apoptosis by activating the p62/Keap1/Nrf2 pathways. Finally, in vivo data showed that CYN inhibited tumour growth in xenografted nude mice. Overall, our findings suggested that CYN may be a promising candidate for the treatment of NB, and the combination of pharmacological inhibitors of autophagy may hold novel therapeutic potential for the treatment of NB. Our paper will contribute to the rational utility and pharmacological studies of CYN in future anticancer research.